Study on incidence of silent cerebral ischemia among diabetic nephropathy patients admitted in tertiary care hospital - Diggikar, P. M.; Satpathy, P. K.; Mishra, Shubham; Dandi, Kranthi (International Journal of Research in Medical Sciences, 2020)
Abstract: Background: Diabetes accelerates the atherosclerotic process in blood vessels, leading to micro- and macro vascular complications, stroke being one of these. Carotid artery atherosclerosis in patients with Diabetic nephropathy is found to be associated with Silent cerebral infarction (SCI). Present study was carried to found any relationship between carotid intima media thickness and silent cerebral infarction in patients with type 2 diabetic nephropathy. Methods: The study was done in 50 DN patients admitted in medicine ward of tertiary care hospital. Subjects were evaluated based on detailed clinical data like symptoms, signs, and associated illnesses, general and systemic examination. Subjects were diagnosed with silent cerebral infarct based on MRI Findings. Each subject had undergone MRI to find out incidence of SCI. Results: Maximum (54%) was in age group of 61-70yrs and very few (6%) were below age of 50yrs. M: F was 1.6:1. Around 44% had duration of diabetes in 1-5yrs of duration and very few (6%) had diabetes >15yrs. On USG scan of carotid vessels it was found that 86% had increased carotid intimal media thickness either or side of vessel. On MRI brain there was incidence of silent cerebral ischemia among 30% study subjects. Conclusion: Both CIMT and SBI showed rise in incidence with corresponds to increase in age, duration of diabetes and urine albumin level among study subjects.